The Use of Domperidone Increases the Completion Rate of Small Bowel Capsule Endoscopy: Does This Come at the Expense of Diagnostic Yield?. Issue 5 (May 2015) - Koulaouzidis, Anastasios; Dimitriadis, Stavros; Douglas, Sarah; Plevris, John N.
Abstract : Background: The completion rate (CR) of small bowel capsule endoscopy (SBCE) has been reported at 81.3% to 84.8%. Prokinetic agents are used to increase CR and (theoretically) diagnostic yield (DY). Domperidone has not been widely used in SBCE; unlike metoclopramide, it lacks extrapyramidal adverse effects. Objectives: This was a retrospective study. This study aimed to assess gastric transit time (GTT), small bowel transit time (SBTT), and the CR of SBCE when using domperidone. Furthermore, we aimed to compare the CR of 2 different SBCE systems (MiroCam, PillCam). Consecutive SBCE examinations (January 2008 to October 2012) from a tertiary referral center were analyzed. Results: In the aforementioned period, a total of 635 SBCE examinations were performed: 379/635 (59.7%) with PillCamSB and 256 (40.3%) with MiroCam. In 437/635 (68.8%) examinations, liquid domperidone (5 mg) was administered for capsule ingestion, whereas 198 (31.2%) ingested the capsule without any domperidone. Although the 2 groups were comparable, the median age of patients who received domperidone was higher compared with patients who did not receive (58 vs. 48 y, P =0.027). In our cohort, the overall CR of SBCE was 88.9%. The 2 SBCE systems showed equivalent CR (PillCamSB 88.9%, MiroCam 89.1%; P =0.96). The use of liquid domperidone increased CR (91.1% vs. 84.3%; P =0.042). Interestingly, the use of domperidone with PillCamSB was associated with reduced DY for vascular, inflammatory, and polyps/mass-type lesions. This effect was not seen in the MiroCam group. Furthermore, the median GTT and the median SBTT did not differ between the 2 groups (GTT/SBTT with domperidone 26.0′/221.0′ and without 29.0′/228.0′, respectively; P =0.461/ P =0.477). A higher CR was noted when domperidone was used with PillCamSB (93.0% vs. 89.5%, P =0.012) than with MiroCam (84.4% vs. 83.3%, P =0.08). Limitations: The major limitations of this study were the retrospective design of the study and limited numbers on MiroCam with no domperidone. Conclusions: In conclusion, the use of domperidone increases the CR of SBCE with PillCamSB. However, this increase does not translate into higher DY. A smart, tailored approach, which may include domperidone, purgatives, and real-time viewers, may be used in the clinical practice to improve DY until technology delivering capsules with much longer battery time becomes available.